FRI0178 Anti-Etanercept Antibodies and Etanercept Leves Levels in Rheumatoid Arthritis Patients Treated with Low and Full-Dose Etanercept in Das28 Remission. (15th July 2016) - Ometto, F.; Beggio, M.; Friso, L.; Astorri, D.; Raffeiner, B.; Botsios, C.; Bernardi, L.; Padoan, R.; Punzi, L.; Ghiraldello, A.; Doria, A.
Abstract : Objectives: To investigate etanercept (ETN) serum levels and anti-etanercept antibodies (AEA) and evaluate whether ETN levels are associated with SDAI remission in rheumatoid arthritis patients in DAS28 remission treated with full-dose (25 mg twice weekly) and low-dose (25 mg once weekly) ETN. Methods: We selected 70 patients in stable (≥12 months) full-dose (35) or low-dose (35) ETN, in remission (DAS28<2.6 for ≥12 months) and with a treatment duration ≥5 years. AEA and basal ETN levels were tested by ELISA. A cut-off >142AU/ml was adopted for defining positive AEA. A concentration of ETN ≥3.1μg/mL was considered as a high ETN level [1]. Multivariate regression analysis was used to investigate whether high ETN levels were associated with SDAI remission. Results: One blood sample in the low-dose group resulted inadequate. AEA were present in 1 patient in low-dose (1/34, 2.9% low-dose ETN vs 0/35, 0% full-dose ETN, p=0.507). Full-dose and a lower weight were associated with high ETN levels: 15/35, 42.9% vs 3/34, 8.8% p=0.001 and 55.0 kg (57.0;80.0) and 65.0 (51.0;69.8), p=0.014 for high and low ETN levels respectively. Lower ETN levels, low-dose and a longer low-dose duration were associated with SDAI remission but were not confirmed with multivariate regression (Table 1 ). Conclusions: AEA are almost absent in patients in stable remission, patient with full-dose ETN and lower weight have higher ETN levels. ETN levels are not predictive of SDAI remission. References: Daïen CI, Daïen V, Parussini E, et al. Etanercept concentration in patients with rheumatoid arthritis and its potential influence on treatment decisions: a pilot study. J Rheumatol 2012.39(8):1533–8. Disclosure of Interest: None declared